Violation of the Principle of Cooperation in the Film Hangout by Raditya Dika - Irfan, Muhammad; Taiman; Amin, Arip (IJESS International Journal of Education and Social Science, 2024)
This study aims to identify violations of the principles of politeness in the film "Hangout" by Raditya Dika. This study uses a qualitative descriptive approach and a pragmatic analysis method based on Grice's cooperative principle theory. The main focus of this study is to explore the forms of violations of the cooperative principle in the film's dialogues, by examining several violated maxims. Referential matching and Dell Hymess' SPEAKING approach are used in data analysis, which are collected through observation and analysis of film documents using the Free Listening and Speaking (SBLC) technique. According to the findings of the analysis, there are 46 violations of the cooperative principle covering several maxims such as quantity, quality, relevance and implementation. The film "Hangout" has several examples of significant violations of the cooperative principle, which highlights the need to understand and apply these rules in everyday interactions to avoid miscommunication.